Chitosan‐based organic/inorganic composite engineered for UV light‐controlled smart pH‐responsive pesticide through in situ photo‐induced generation of acid. Issue 6 (14th March 2022) - Liu, Bin; Chen, Chaowen; Teng, Guopeng; Tian, Geng; Zhang, Guilong; Gao, Yujie; Zhang, Lihong; Wu, Zhengyan; Zhang, Jia
Abstract: BACKGROUND: Confined by the volatile property, pesticides are overused and lost significantly during and after spraying, weakening the ecological microbalance among different species of lives. Acid‐responsive pesticide is a type of smartly engineered pesticides that contribute to the improvement of utilization efficiency of pesticidal active ingredients in acid‐controlled manner, whilst the implementation of acidic solutions may disturb the balance of microenvironment surrounding targeted plants or cause secondary pollution, underscoring the input of acid in a more precise strategy. RESULTS: Chitosan was chemically modified with a photoacid generator (2‐nitrobenzaldehyde) serving as a light‐maneuvered acid self‐supplier, based on which a smart pesticide was formulated by the integration of attapulgite and organophosphate insecticide chlorpyrifos. Under the irradiation of UV light (365 nm), the modified chitosan would undergo a photolytic reaction to generate an acid and pristine chitosan, which seized the labile protons and facilitated the release of chlorpyrifos based on its inherent pH‐responsive flexibility. According to the pesticide release performance, the release rate of chlorpyrifos under UV light (27.2 mW/cm 2 ) reached 78%, significantly higher than those under sunlight (22%, 4.2 mW/cm 2 ) and in the dark (20%) within the same time, consistent with the pH reduction to 5.3 under UV light and no obvious pH change for the two other situations, exhibiting an attractive UV light‐controlled, acid‐propelled release behavior. CONCLUSION: Compared to direct acid spray approach, the proposed in situ photo‐induced generation of acid locally on the spots of applied pesticide circumvents the problem of acid contamination to nontargets, demonstrating higher efficiency and biocompatibility for the controlled delivery of acid‐responsive pesticides and pest management. © 2022 Society of Chemical Industry. Abstract : Compared to traditional chitosan‐based pH‐responsive pesticide, the proposed in situ photo‐induced generation of acid on the locations of applied pesticide circumvents the problem of acid contamination to nontargets, showing higher efficiency and environmental friendliness for management of pests.